Measurements, Modelling and Simulation of Dynamic Systems - Layer, Edward; Tomczyk, Krzysztof; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book discusses an analog-to-digital system intended to dynamic measurement, particularly for non-electrical quantities. The construction and properties of measurement sensors are analyzed in detail, as these represent the primary components for all measurement systems. Procedures for signal noise reduction are presented based on the time window function and a digital Kalman filter. Also covered in this book are the methods of modeling, model development and identification procedures on the basis of measurement data. The theory of maximum errors is applied in order to determine mapping errors of models in case of non-standard input signals. This is based on signals maximizing the chosen error functional. The existence and attainability of such signals is proved and the algorithms for their determination are presented. Detailed calculation methods, based on dedicated numerical procedures are demonstrated, which allow the integral-square error as well as the absolute error to be determined. The problems presented in the book are relevant to a wide range of applications where there is a requirement to determine the accuracy of indeterminate dynamic signals such as occurs in the fields of engineering, medicine, biology, physics etc. This book will interest researchers, scientists, engineers and graduate students in many disciplines, who make use of measurements, modelling and computer simulation.
to Measuring Systems -- Sensors -- Methods of Noise Reduction -- Model Development -- Mapping Error.
Keywords: Engineering; Information systems; Artificial intelligence; Engineering mathematics; Electronics; Engineering; Appl.Mathematics/Computational Methods of Engineering; Electronics and Microelectronics, Instrumentation; Artificial Intelligence (incl. Robotics).; Information Systems and Communication Service